2020
DOI: 10.1002/path.5455
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte pathology exceeds axonal pathology in white matter in human amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease. The majority of cases are sporadic (sALS), while the most common inherited form is due to C9orf72 mutation (C9ALS). A high burden of inclusion pathology is seen in glia (including oligodendrocytes) in ALS, especially in C9ALS. Myelin basic protein (MBP) messenger RNA (mRNA) must be transported to oligodendrocyte processes for myelination, a possible vulnerability for normal function. TDP43 is found in pathological inclusions in ALS and is a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…Enhanced MLKL expression was also observed in CTXLP + OPCs in the spinal tissue from patients with ALS, which may not causally link to necroptosis per se, but with myelin breakdown and regeneration [76]. Our work supports the accumulating evidence of OL pathology in ALS [101] and points to CTXLP as also having a potential role in OL pathology in a select subset of ALS cases.…”
Section: Discussionsupporting
confidence: 73%
“…Enhanced MLKL expression was also observed in CTXLP + OPCs in the spinal tissue from patients with ALS, which may not causally link to necroptosis per se, but with myelin breakdown and regeneration [76]. Our work supports the accumulating evidence of OL pathology in ALS [101] and points to CTXLP as also having a potential role in OL pathology in a select subset of ALS cases.…”
Section: Discussionsupporting
confidence: 73%
“…HyperphosphorylatedTDP-43 inclusions were only found in the white matter in subcortical regions directly associated with the motor and sensory cortices, with an absence of any overt pathology in axonal pathways [143]. However, a recent study has suggested that TDP-43 and p62 aggregates in ALS patient oligodendrocytes are a major pathogenic burden [144], thus more work is required to fully understand the extent to which these cells are involved in pathology progression.…”
Section: Non-cell Autonomous Effectsmentioning
confidence: 99%
“…However, whether an increase in oligodendrocyte density occurs by P90 remains to be determined. In a similar manner, the accumulation of other myelin gene products in the amyelinating oligodendrocytes of Mbp null shiverer mice, including the prominent Plp transcript and protein, show little change from WT [ 67 , 68 ]. Further, the rate of initiation of their truncated Mbp transcript also tracks closely that of WT [ 69 ].…”
Section: Discussionmentioning
confidence: 99%